Paving way for sustainable earth-abundant metal based catalysts for chemical fixation of CO2 into epoxides for cyclic carbonate formation. Issue 2 (3rd April 2022) - Prasad, Divya; Patil, Komal N.; Chaudhari, Nitin K.; Kim, Hern; Nagaraja, Bhari Mallanna; Jadhav, Arvind H.
ABSTRACT: The involvement of CO2 as a renewable and abundant feedstock toward a carbon balanced future has led to production of several value-added products. The primary focus in the current effort is to assess fixation of CO2 and epoxides into cyclic carbonates by employing state-of-the-art metal complexes as promising catalytic systems. Our attention is restricted to Earth-abundant metals such as aluminum, cobalt, iron, zinc and few transition metals in association with different ligand skeletons used for the structural construction of the respective complexes. This review sequentially categorizes these complexes and provides a panoramic overview of their selective catalytic activities and mechanistic understandings based on experimental and theoretical evidences.